Coral Recruitment Spatial Distribution in its Relation With Coral Cover and Herbivorous Fish Abundance Within Conservation Area - Zulfikar Afandy; Ario Damar; Syamsul Bahri Agus (ILMU KELAUTAN: Indonesian Journal of Marine Sciences, 2019)
The continuity of coral reef ecosystem highly depends on the new coral larvae recruitment process. Hence, the information regarding distribution, the abundance of corals, and its relation to other variables are highly important in that ecosystem management. Research was conducted at nine stations represented each zone at the conservation area of Kapoposang Marine Tourism Park (TWP Kapoposang). This research aims at seeking for spatial variations of the abundance of coral recruitment at three primary zones monitored (core zone, sustainable fishing zone and utilization zone) and we further identified its relations with spatial variation of herbivorous fishes abundance and  coral cover’s condition at those zones. The coral recruitment observation employed transect quadrat sampling method with size of 1x1 meter and 10 times repetition at a similar depth, and the coral recruitment abundance measurement in natural habitat based on the amounts of juvenile corals has been defined as coral colony with size of ≤10 cm. Overall, this research has found 534 coral juveniles consisted of 19 genera and 7 families, and the average of juvenile coral density stood at 5.34±4.45 SE.m-2. The coral reef recruitment category at TWP Kapoposang could be classified as high and its abundance spatial distribution showed no significant differences between each zone, as well as not influenced by either herbivorous fish abundance variable or the percentage of live coral cover.